2024
DOI: 10.1101/2024.01.30.578016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial community function increases host plant leaf growth in a pitcher plant experimental system

Jessica R Bernardin,
Erica B Young,
Sarah M Gray
et al.

Abstract: Across diverse ecosystems, bacteria and their host organisms engage in complex relationships having negative, neutral, or positive effects. However, the specific effects of leaf-associated bacterial community functions on plant growth are poorly understood. This study investigated mechanistic relationships between bacterial community function and host plant growth in a carnivorous plant that relies on microbes to break down insect prey via extracellular hydrolytic enzymes. Sterile, freshly opened leaves (pitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 106 publications
(188 reference statements)
0
1
0
Order By: Relevance
“…The carnivorous purple pitcher plant, Sarracenia purpurea, offers a unique opportunity to test how arthropod substrates affect microbial function and composition in a small, natural, freshwater system under semi-controlled conditions. The microbial communities that develop inside purple pitcher plants rely on the plant to capture arthropod prey, and the plant relies on the microbial community it hosts to break down that prey and release nutrients that are severely limited in the soils in which it grows ( 28 30 ). Evidence from a recent study showed that the presence or absence of prey additions affected microbial community functions like hydrolytic enzyme activity, including chitinase and protease enzymes, which in turn were linked to the transformation of insect nutrients into more plant-available forms ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The carnivorous purple pitcher plant, Sarracenia purpurea, offers a unique opportunity to test how arthropod substrates affect microbial function and composition in a small, natural, freshwater system under semi-controlled conditions. The microbial communities that develop inside purple pitcher plants rely on the plant to capture arthropod prey, and the plant relies on the microbial community it hosts to break down that prey and release nutrients that are severely limited in the soils in which it grows ( 28 30 ). Evidence from a recent study showed that the presence or absence of prey additions affected microbial community functions like hydrolytic enzyme activity, including chitinase and protease enzymes, which in turn were linked to the transformation of insect nutrients into more plant-available forms ( 31 ).…”
Section: Introductionmentioning
confidence: 99%